DAMAGE CAUSES OF EUROPEAN ASH IN THE PERMANENT SAMPLING PLOTS IN KHARKIV REGION - Meshkova, V. L.; Borysova, V. L. (Forestry and Forest Melioration, 2018)
Introduction European (common) ash (Fraxinus excelsior L.) is one of the main forest-forming species in broadleaved forests of the Left-bank Forest-Steppe of Ukraine. The health condition of ash species recently has attracted increased attention because of its large-scale decline in many European countries, mainly as a result of ash dieback disease caused by invasive fungus Hymenoscyphus fraxineus. This disease is proved to spread in the region of our research, but the occurrence is relatively low or is poorly diagnosed. Apart from this disease, wood decay fungi, foliage browsing and xylophagous insects, as well as bacterial cancer play an appreciable role in ash decline. However, the spread of different causes of ash decline in the same stands was not studied before in the Left-bank forest-steppe zone of Ukraine. The aim of the research was to estimate European ash health condition and occurrence of certain damage types in permanent sample plots in Kharkiv region. Materials and Methods The investigations were carried out in 2016–2017 on 22 permanent sample plots in forest stands with European ash participation of Skrypayivske Training & Experimental Forest Enterprise and Chuguyevo-Babchanske Forest Enterprise (Kharkiv region). The survey covered 2,112 trees of European ash of 18–110 years old. Defoliation of ash was evaluated visually with an accuracy of 5 % at the end of June (after insects-defoliators completing feeding in this tree species). Category of health condition was evaluated on a range of visual characteristics (1st – healthy; 2nd – weakened; 3rd – severely weakened; 4th – drying; 5th – recently died; 6th – died over a year ago). Index of health condition (Ic) for forest stand was calculated as mean weighted from trees number of each category of health condition. All visible symptoms and signs of each tree damage were registered. The occurrence of each type of damage was evaluated as the part of trees with respective symptoms or signs. Weather parameters were taken from Zmiyiv meteorological station in Kharkiv region (49°41’ N, 36°21’ E). The statistical analyses included calculation of the mean and standard error of estimated parameters as well as a correlation between tree age and occurrence of different damage types (MS Excel). Results and Conclusions Following eight types of damage were revealed in inspected ash stands: frost cracks, mechanical damage of stems, epicormic shoots, branch dieback, symptoms of a bacterial disease and butt rot, signs of wood destroying fungi and insect feeding. Branch dieback and butt rot dominated with the occurrence of 52 and 39 % respectively. In the stands of vegetative origin in fresh fertile forest site conditions, the stand age correlation with forest health condition, with occurrence of bacterial disease, branch dieback, and insect damage was significant. Percentage of trees with butt rots, branch dieback, and epicormic shoots was significantly higher in moist fertile forest site conditions than in fresh fertile forest site conditions. In young stands (20–30 years old) significantly higher occurrence of the bacterial disease of ash, epicormic shoots, butt rot, and mechanical damage of stems was registered more often in moist fairly fertile forest site conditions than in fresh fairly fertile forest site conditions. 9 Figs., 3 Tables, 17 Refs.